“The taking-something-to-be-true [that] cannot be communicated”: remarks on the (lack of) communicability to understand the problem of social irrationality - Guimarães, Rômulo Eisinger (Studia Kantiana, 2023)
Since learning how “to make use of your own Understanding” (WA, AA 08: 35), and “seeking the supreme touchstone of truth in oneself (i.e., in one’s own Reason)” (WDO, AA 08: 146, footnote) – in a word: to enlighten oneself – is a process; and since Reason, in such a process, “needs attempts, practice and instruction” (IaG, AA 08: 19), it is only slowly that one can arrive at Enlightenment (cf. WA, AA 08: 36). As a matter of fact, the process of Enlightenment involves culture, i.e. the cultivation of the human being and his or her rational predispositions. And of fundamental importance in this process are communicability, participation and publicity – i.e., the possibility of making an idea public. Now, since these abilities are so important for Enlightenment, everything that does not allow the communication of ideas and thoughts to each and every human being is diametrically opposed to this process. This seems to be the case with the phenomenon of social irrationality and cognitive vices. The present paper aims to highlight how the problem of (lack of) communicability proves essential to understanding the phenomenon of social irrationality.